Metabolomic Profiling of Schisandra chinensis (Turcz.) Baill Leaves and Their Combined Effects with Malus domestica Borkh Powder and Beta vulgaris L. on Experimental Dental Germ Histogenesis: Schisandra metabolomic profile and its effect on dental histogenesis - Khalitovna, Galiakhmetova Elvira; Vladimirovna, Kudashkina Natalia; Rashitovna, Khasanova Svetlana; Sergeevich, Chuikin Oleg; Ansafovna, Petrenko Alfina; Vyacheslavovna, Makusheva Natalia; Farnam, Golrokh (Iranian Journal of Pharmaceutical Sciences, 2025)
Schisandra chinensis, a classical natural adaptogen, is utilized in official medicine for its fruits and seeds due to its pharmacological properties, such as adaptogenic, immunostimulating, antioxidant, hepatoprotective, antitumor, and membrane-stabilizing effects. These properties are attributed to a complex of biologically active substances, including lignans, essential oils, polysaccharides, triterpene saponins, vitamins, and macro- and microelements. The study also explores the potential use of plants with various biological components and detoxifying effects, using the example of histogenesis changes in jaw bone tissue and dental rudiments of laboratory animals exposed to ecotoxicants. These ecotoxicants, even in small doses, exhibit strong mutagenic and carcinogenic effects with high cumulative ability and toxicity. The research focuses on identifying marker components with physiological activity in the metabolic profile of Schisandra chinensis leaves and examining the impact of its extract, combined with Malus domestica and Beta vulgaris powders, on dental bud histogenesis. Gas chromatography with a mass-selective detector (GC/MS) was used to analyze three Schisandra chinensis leaf extract samples, identifying 34 organic compounds, primarily hydrocarbons, lignans, and terpenoids. Chloroform-based extracts contained the highest number of compounds. The effect of ecotoxicants on rat jaw tissues and dental rudiments was examined in five experimental groups via histological microscopy. Various degrees of dental histogenesis abnormalities and structural changes in dental tissues were observed, including impaired blood circulation, histogenesis of dental rudiments, and viability of ameloblasts and odontoblasts during dental hard tissue formation. Pregnant rats exposed to ecotoxicants and treated with a mixture of Malus domestica, Beta vulgaris powders, and Schisandra chinensis leaf extract gave birth to offspring with fewer dental rudiment and tissue changes.